2003
DOI: 10.1002/em.10178
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assessment of mutagenicity and clastogenicity of BDE‐99, a pentabrominated diphenyl ether flame retardant

Abstract: Polybrominated diphenyl ethers (PBDEs), which are widely used as flame retardants, are considered persistent organic pollutants. To date, the available toxicological data on PBDEs are limited and were primarily obtained by studying technical blends. The present study was undertaken to investigate the genotoxicity of the pure congener 2,2',4,4',5-brominated diphenyl ether (BDE-99), one of the major isomers present in penta-commercial products. Bacterial reverse mutation assays in Salmonella typhimurium strains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
(27 reference statements)
1
6
0
Order By: Relevance
“…In the present study, we demonstrated that 10 −10 to 10 −4 M BDE-99 has limited effects on the proliferation of colorectal HCT-116 cells. This finding is consistent with a previous study showing that the frequency of structural chromosome aberrations was not significantly higher than the control and no sign of cytotoxicity was observed in BDE-99-treated Allium cepa (26). The study of Slotkin et al also showed that growth of PC12 cells was unimpaired by BDE-99 at 50 μM (27).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we demonstrated that 10 −10 to 10 −4 M BDE-99 has limited effects on the proliferation of colorectal HCT-116 cells. This finding is consistent with a previous study showing that the frequency of structural chromosome aberrations was not significantly higher than the control and no sign of cytotoxicity was observed in BDE-99-treated Allium cepa (26). The study of Slotkin et al also showed that growth of PC12 cells was unimpaired by BDE-99 at 50 μM (27).…”
Section: Discussionsupporting
confidence: 93%
“…did not induce gene mutations in the Ames test neither chromosomal aberration in the Allium test (Evandri et al, 2003).…”
Section: Bde-99mentioning
confidence: 80%
“…For instance, in subchronic toxicity studies in rat, NOEL (no-observed-effect-level) values are usually in the g/kg/day range for decaBDE, but less than 10 mg/kg/day for pentaBDE ). PBDEs are not genotoxic (Hardy, 2002;Evandri et al 2003), but an increased incidence of hepatocellular carcinomas and of thyroid adenomas have been observed in rodents upon exposure to BDE-209 (NTP, 1986;Darnerud et al 2001). Reproductive toxicity has also been reported.…”
Section: Toxicity Of Pbdesmentioning
confidence: 99%